Antibacterial Activities of Thymol, Eugenol and Nisin Against Some Food Spoilage Bacteria - Panitee Tippayatum; Vanee Chonhenchob (Agriculture and Natural Resources, 2007)
Antibacterial activities of nisin, thymol and eugenol were assayed against four strains of common spoilage bacteria, so as to introduce into food packaging material for shelf-life benefit. Those bacterial strains included E. coli ATCC 25922 DMST 4212, S. aureus ATCC 25923 DMST 8840, B. cereus ATCC 11778 DMST 5040 and L. monocytogenes DMST 17303 were used for this study by agar well diffusion test on nutrient agar. The active inoculum size between 105-106 cfu/g of each strain was inoculated into the sterile warmed liquefied medium, prior to plate pouring. After solidified, holes of 5 mm in diameter were punctured using a sterilized cork borer # 2. Then, an individual of 40 μl two-fold serial dilution from each agent was applied for MIC determination with experimental design for three replicates. Results of clear zones were reported after 24 hr incubation at 37 °C. It was found that MICs for thymol, eugenol and nisin was between 3-5, 8-11 and 4-23 mg/ml, respectively, depending on each bacterial strain tested. This was concluded that thymol appeared to be the most preferable agent for future research in active food packaging development, especially in term of antimicrobial benefit.